An elaborate structure investigation of the chiral polymorph A-enriched zeolite beta. Issue 10 (16th February 2016) - Tong, Mingquan; Zhang, Daliang; Zhu, Liangkui; Xu, Jun; Deng, Feng; Xu, Ruren; Yan, Wenfu
Abstract : The polymorph percentage and the chirality of the synthesized polymorph A-enriched zeolite beta was investigated by combining the XRD, NMR, HRTEM and the DIFFaX simulation. A domain with 14 channel-layers of polymorph A was found, which was very rare in the crystals of zeolite beta. Abstract : Polymorph A-enriched zeolite beta was hydrothermally synthesized from an extremely concentrated system using tetraethylammonium hydroxide (TEAOH) as an organic structure-directing agent (OSDA) in the presence of fluoride. The sample was investigated by powder X-ray diffraction (XRD), 29 Si magic angle spinning nuclear magnetic resonance (MAS NMR), 19 F MAS NMR, and high-resolution transmission electron microscopy (HRTEM). The polymorph A enrichment was confirmed by the characterization, and the percentage of polymorph A was determined to be approximately 66% by DIFFaX simulation and HRTEM analyses. A pure polymorph A stacking area was detected by HRTEM, and the chiral structure of polymorph A in the zeolite beta was investigated on the basis of the HRTEM images.